Bacterial chromatin: converging views at different scales. (June 2016) - Dame, Remus T; Tark-Dame, Mariliis
Abstract : Bacterial genomes are functionally organized and compactly folded into a structure referred to as bacterial chromatin or the nucleoid. An important role in genome folding is attributed to Nucleoid-Associated Proteins, also referred to as bacterial chromatin proteins. Although a lot of molecular insight in the mechanisms of operation of these proteins has been generated in the test tube, knowledge on genome organization in the cellular context is still lagging behind severely. Here, we discuss important advances in the understanding of three-dimensional genome organization due to the application of Chromosome Conformation Capture and super-resolution microscopy techniques. We focus on bacterial chromatin proteins whose proposed role in genome organization is supported by these approaches. Moreover, we discuss recent insights into the interrelationship between genome organization and genome activity/stability in bacteria.